Needs Analysis: The Primary Step in Designing English Instructional Materials for Nursing Students - Muhammad Nashir; Roudlotun Nurul Laili; Sholihin Sholihin; Wahyu Adri Wirawati (Acitya: Journal of Teaching and Education, 2022)
This research intended to analyze and identify the needs of English instructional materials (ESP) for nursing students. English in higher education in non-English major is only as a General Basic Subject and the material provided is only general English. Whereas ideally English material taught should be adjusted to their major. So, needs analysis was required to find out the need for English teaching materials on the nursing department so that students could get the appropriate materials they really need to support their future careers to be professional nurses. This study design was a descriptive qualitative with subjects were 81 nursing students, heads of nursing study programs, 3 ESP lecturers, 2 Indonesian nurses, 2 Indonesian nurses who work in overseas hospital. The research instrument used a questionnaire and interviews. The results showed that in general, students' English skills were still low. From the 4 language skills, speaking become the main priority to provide them fulfilling their profession’s demands in accordance with the job market, namely being able to communicate in English well. They also expected ESP English teaching materials that are relevant to nursing major to support their professional careers. 86% students believed if English materials related to nursing major will improve their interest in learning. Besides that, there are also 12 nursing topics that students need to support their world of work later. This research results will be guidance in making appropriate syllabus and developing English for nursing textbook.